THE EFFECT OF OXYTOCIN MASSAGE ON ANXIETY CHANGES IN BREASTFEEDING MOTHER - Kunawati Tungga Dewi (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Anxiety that occurs in breastfeeding mothers is caused by various factors. Anxiety can reduce the hormone prolactin and oxytocin secretion so that breast milk production will be reduced. Oxytocin massage is a non-pharmacological therapy that is often performed to reduce anxiety and increase milk production. Oxytocin massage is a massage along the spine to the fifth-sixth rib to facilitate milk production. Objective: This study aims to determine the effect of oxytocin massage on the anxiety changes of a breastfeeding mother. Methods: This research was qualitative (case report) conducted on a 21 years old breastfeeding mother with a psychological problem in the form of anxiety. The subject complained of anxiety because breastmilk production is a little. She said it is her first baby and currently lives with her husband and mother-in-law. The subject wants to give exclusive breastfeeding to her baby. However, when the baby is fussy, the mother-in-law always suggests giving formula milk. Subjects had a history of caesarian section delivery and post-hospitalization due to wound infection. The assessment was carried out in the form of anamnesis and examination using HARS. Results: The results of the HARS showed that the mother was in the mild anxiety category. The intervention given in this case is oxytocin massage therapy was carried out for 7 days. Then in the evaluation, the mother showed a decrease in anxiety after the oxytocin massage therapy. Conclusion: Oxytocin massage can help mothers relax, reduce stress and increase milk production. Keywords: anxiety oxytocin massage, mother breastfeeding.